2015
DOI: 10.12694/scpe.v16i2.1085
|View full text |Cite
|
Sign up to set email alerts
|

Multiple String Matching on a GPU using CUDAs

Abstract: Multiple pattern matching algorithms are used to locate the occurrences of patterns from a finite pattern set in a large input string. Aho-Corasick, Set Horspool, Set Backward Oracle Matching, Wu-Manber and SOG, five of the most well known algorithms for multiple matching require an increased computing power, particularly in cases where large-size datasets must be processed, as is common in computational biology applications. Over the past years, Graphics Processing Units (GPUs) have evolved to powerful parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For the PRK, the parameters q = 65521, which is the largest prime number less than 2 16 , and d = 2 were used. In terms of the number τ of threads, step 2 of the PRK uses one CUDA thread for each pattern and compute the values of h(P k ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the PRK, the parameters q = 65521, which is the largest prime number less than 2 16 , and d = 2 were used. In terms of the number τ of threads, step 2 of the PRK uses one CUDA thread for each pattern and compute the values of h(P k ).…”
Section: Resultsmentioning
confidence: 99%
“…The proposed CUDA-based implementation outperformed a quad-core processor providing speedup of up to 14 times. Kouzinopoulos et al [16] evaluated several multiple pattern matching algorithms on the GPU. They reported that even a basic implementation of these algorithms in the GPU were between 2.5 and 10.9 faster than a single core CPU implementation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the most widely used algorithm for processing multiple patterns is the AC algorithm. In addition to this algorithm, the Commentz-Walter [33] and Wu-Manber (WM) algorithms [34,35] are used to process multiple patterns. The AC algorithm and parallel pattern matching algorithm are explained in the subsequent paragraphs.…”
Section: Related Workmentioning
confidence: 99%
“…In 2015, Kouzinopoulos [23] did an experiment using a GTX 280 GPU and a Xeon 2.4GHz CPU. They tested the Aho-Corasick, Set Horspool, Set Backward Oracle Matching, Wu-Manber and SOG multiple pattern matching algorithms showing the basic implementation of these algorithm in GPU were between 2.5 and 10.9 faster than the CPU implementation.…”
Section: Improvements To String Matching In Gpu Using Cudamentioning
confidence: 99%